One-to-one laptops in a public secondary school: students' usage and the impact on achievement - Clarke, E. Jason, author; Gloeckner, Gene, advisor; O'Donnell-Allen, Cindy, committee member; Mallette, Dawn, committee member; Birmingham, Daniel, committee member (Colorado State University. Libraries, 2016)
Computer technology has become ubiquitous in the lives of today's learners. Schools and districts are responding to the rise of technology with a push to expand access to computers for all students in the form of one-to-one laptop initiatives. While such initiatives have been shown to help students develop computer and technology skills, their impact on achievement has been more difficult to ascertain. Differences in implementation levels between different schools, teachers, and students, have made the relationship between laptop use and achievement difficult to measure. This study was designed to provide more information regarding the relationship between different types and frequencies of laptop usage and student reading achievement, as well as the barriers and opportunities which limit or promote the use of the laptops by students and teachers. This study used a mixed methods design incorporating both qualitative and quantitative data and analysis. Three hundred and fifty-five 9th and 10th grade students at a public high school which was in the fifth year of a one-to-one laptop initiative were surveyed regarding the specific ways in which they used their district-provided laptop computers. These findings were matched with individual achievement scores on the MAP reading test and statistical correlations were run between specific types and frequencies of laptop use and achievement. In addition, three teachers were interviewed regarding the barriers to the use of the laptops they had faced and the resources and skills which enabled their successful integration. The quantitative findings of the study indicate that using the laptops for homework and outside the classroom learning are significantly correlated with high reading achievement. They also indicate that activities such as social networking, playing games, and contributing to online databases were significantly correlated with low reading achievement. The qualitative findings showed that student lack of access to Wi-Fi at home, the ability level of students, and specific content-area concerns were significant barriers to the incorporation of the laptops into the learning process. They also indicated that ongoing professional development and teacher perseverance were keys to the successful integration of the laptop computers into the teaching and learning process.